The Innovation of Seaweed Processing Process into Chips as a Local Food Superior Product - Prayetno, Eko; Mirnawati; Rahayu, M. Ageng; Susilo, Akhbar (Jurnal Al Maesarah, 2025)
This community service aims to introduce innovations in the process of processing seaweed into chips as a superior local food product in Wanci Coastal Village. This village has a great potential in seaweed production, but its utilisation is still limited to raw products, so the added value for the local community is not optimal. Through this activity, technology transfer was conducted to process seaweed into chips using simple yet efficient drying and frying methods. The training involved farmer groups and housewives as the main actors. The results showed that this innovation not only improved the technical skills of the community, but also opened up new business opportunities with products that are highly competitive in the local market. The response from the community was very positive, as seen from the increase in production and market demand. Thus, this programme is expected to become a model for other coastal areas in developing the potential of local natural resources in a sustainable manner.